2022
DOI: 10.3389/fpsyg.2022.857585
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Equity Disputes in Listed Companies With Dispersed Ownership Structure and Protection of Small and Medium Shareholders’ Interests

Abstract: This paper selected Vanke as the case to study the governance problems of Vanke and the protection of the interests of small and medium shareholders under the situation of equity disputes. At the same time, the study further explored the advantages and disadvantages of the dispersed ownership structure, the long-term impact on the company’s development and the choice of the involved corporate governance methods under the current Chinese capital market conditions. This paper adopted the event research method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…The second type of agency problem of principal-agent theory points out that a large shareholding of major shareholders and concentrated ownership cause conflicts of interests between major shareholders and minority shareholders, and major shareholders may encroach on the interests of minority shareholders. Therefore, a balance mechanism needs to be formed among the shareholders of the company, which can provide the relatively small shareholders with the right to obtain consultation and resolve the conflict of interest among the shareholders of the enterprise [45]. The study of Laeven and Levine (2004) [46] showed that even distribution of equity balance in listed companies is conducive to promoting corporate performance.…”
Section: Ownership Structure and Firm Valuementioning
confidence: 99%
“…The second type of agency problem of principal-agent theory points out that a large shareholding of major shareholders and concentrated ownership cause conflicts of interests between major shareholders and minority shareholders, and major shareholders may encroach on the interests of minority shareholders. Therefore, a balance mechanism needs to be formed among the shareholders of the company, which can provide the relatively small shareholders with the right to obtain consultation and resolve the conflict of interest among the shareholders of the enterprise [45]. The study of Laeven and Levine (2004) [46] showed that even distribution of equity balance in listed companies is conducive to promoting corporate performance.…”
Section: Ownership Structure and Firm Valuementioning
confidence: 99%
“…Concentrated ownership has a positive effect on the performance of companies in Asia, where large shareholders can manage resources effectively to obtain maximum company performance results (Aboud & Diab, 2022;Heugens et al, 2009;Nguyen et al, 2015;Thomsen & Pedersen, 2000), include to influence policies regarding the application of ESG principles (Albitar et al, 2020). The dispersion of ownership in the presence of large and medium shareholders in addition to the main shareholders can be an internal control over company management (He et al, 2022). Therefore, the equity balance between 2 nd until 5 th largest shareholder to the main shareholder may also influence the ESG relation to company performance.…”
Section: Introductionmentioning
confidence: 99%
“…28 Empirical work has also shown that dispersed ownership is likely to cause equity disputes. 29 In the same vein, though, firms may be able to avoid diseconomies of scale, particularly organisational diseconomies, if billionaires are banned and the ownership is more evenly distributed. Research has shown that smaller firms can retain employees and solve problems better in certain industries such as R&D in comparison to bigger firms, who have to deal with organisational diseconomies of scale.…”
mentioning
confidence: 99%